Can a Public and Patient Involvement (PPI) Informed Participant Information Leaflet (PIL) Improve Trial Recruitment, Retention, and Quality of Decision Making? Results of a Randomised Controlled Double‐Blind Study Within a Trial (SWAT) - Linda O'Neill; Peter Knapp; Suzanne L. Doyle; Sanela Begic; Emily Smyth; Neil Kearney; Sophie Grehan; Adwoa Parker; Peter Browne; Ricardo Segurado; Deirdre Connolly; Jacintha O'Sullivan; et al. (Health Expectations, 2025)
ABSTRACT Introduction Public and patient involvement (PPI) may be utilised to improve aspects of trial conduct. This study within a trial (SWAT) aimed to examine if a PPI‐informed participant information leaflet (PIL) could improve recruitment, retention, and quality of decision‐making of an exercise‐based rehabilitation trial (RESTORE II) for upper gastrointestinal (UGI) cancer survivors. Methods This SWAT was conducted over two phases. Phase 1 applied qualitative methods to develop and refine a PPI‐informed PIL. Phase 2 embedded a randomised controlled double‐blind SWAT within the RESTORE II trial, comparing a standard PIL (PIL A) to the PPI‐informed PIL (PIL B) in terms of recruitment, retention, and quality of decision‐making (Decision Making Questionnaire [DMQ]). Results Phase 1 recruited 16 PPI members (mean age 67.01 [9.28] years, mostly male [81.25%] and all UGI cancer survivors). Participants reviewed the standard PIL A and made suggestions for improvement, including revisions to the layout, title, text, provision of key information on the first page, and greater emphasis on the potential benefits of participation. This feedback was used to draft the alternative PIL B, which the Phase 1 participants reviewed and refined through minor changes to the appearance, text, and layout. In Phase 2, 307 potential RESTORE II trial participants were randomised to receive either PIL A (n = 154) or PIL B (n = 153). The overall recruitment rate was 28.7%. (PIL A 26.6% vs. PIL B 30.7%, OR 1.22 [95% CI 0.74 to 2.01, p = 0.43]), retention was 84.1% (PIL A 85.4% vs. PIL B 83.0%, OR 0.84 [95% CI 0.26 to 2.65, p = 0.760]). No significant difference in mean (SD) DMQ scores was observed: PIL A: 29.1 (4.4) vs. PIL B: 29.1 (5.1) (mean difference 0.03, 95% CI −1.64 to 1.69, p = 0.49). Conclusions A PPI‐informed PIL did not improve recruitment, retention, or decision‐making for the RESTORE II trial. Patient or Public Contribution Patients with UGI cancer informed the development of the interventional PIL B. Author P.B. provided input from the patient's perspective throughout the SWAT as a member of the Trial Steering Committee, providing oversight to the SWAT management, and contributed to analysis and the production of this manuscript. Trial Registration SWAT Registration: The Northern Ireland Hub for Trials Methodology Research, SWAT Store, SWAT 100 https://www.qub.ac.uk/sites/TheNorthernIrelandNetworkforTrialsMethodologyResearch/FileStore/Filetoupload,914713,en.pdf. Host Trial Registration Clinical Trials. gov https://clinicaltrials.gov/study/NCT03958019.